(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the integration of intercomprehension strategies in the simultaneous teaching of German and French, two prominent languages in European multilingual contexts. Intercomprehension is a process where speakers of one language understand another related language without actively speaking it. It offers a promising path toward more efficient and inclusive language education. Drawing on recent developments in multilingual pedagogy, the research investigates how intercomprehension can foster metalinguistic awareness, cross-linguistic transfer, and learner autonomy. Through qualitative analysis of instructional design and teacher reflections, the study identifies practical methods for integrating intercomprehension into language classrooms and highlights its implications for curricular innovation.